2010
DOI: 10.1016/j.jcpa.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Aetiological Agents of Proliferative and Necrotizing Pneumonia in Italian Pigs

Abstract: SummaryProliferative and necrotizing pneumonia (PNP) is a form of interstitial pneumonia that occurs in weaning and post-weaning pigs. PNP is characterized by hypertrophy and hyperplasia of type II pneumocytes and coagulative necrosis and granular debris within alveolar spaces. Canadian and European studies suggest that the porcine reproductive and respiratory syndrome virus (PRRSV) and porcine circovirus type 2 (PCV2) are the main causes of the disease, but Aujezsky's disease virus (ADV) and swine influenza v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
4
10
0
1
Order By: Relevance
“…PRRSV was implicated very early as being important in the pathogenesis of PCVAD. Not surprisingly, several field studies conducted in Spain (Grau-Roma and Segalés, 2007;Segalés et al, 2002), the United States (Dorr et al, 2007;Pallarés et al, 2002;Pogranichniy et al, 2002), the Netherlands (Wellenberg et al, 2004), Canada (Drolet et al, 2003), and Italy (Morandi et al, 2010) confirmed the interaction of PRRSV and PCV2. For example, a case-control study in the Netherlands, which included 60 clinically affected pigs and 180 pigs without clinical signs, identified combined PCV2 and PRRSV infection in 83% of the clinically-affected pigs and in 35% of the pigs from PCVAD-free herds (Wellenberg et al, 2004).…”
Section: Porcine Reproductive and Respiratory Syndrome Virusmentioning
confidence: 87%
See 1 more Smart Citation
“…PRRSV was implicated very early as being important in the pathogenesis of PCVAD. Not surprisingly, several field studies conducted in Spain (Grau-Roma and Segalés, 2007;Segalés et al, 2002), the United States (Dorr et al, 2007;Pallarés et al, 2002;Pogranichniy et al, 2002), the Netherlands (Wellenberg et al, 2004), Canada (Drolet et al, 2003), and Italy (Morandi et al, 2010) confirmed the interaction of PRRSV and PCV2. For example, a case-control study in the Netherlands, which included 60 clinically affected pigs and 180 pigs without clinical signs, identified combined PCV2 and PRRSV infection in 83% of the clinically-affected pigs and in 35% of the pigs from PCVAD-free herds (Wellenberg et al, 2004).…”
Section: Porcine Reproductive and Respiratory Syndrome Virusmentioning
confidence: 87%
“…A case-control study in the United States, which included 31 pigs with a clinical history of wasting and microscopic lesions characteristic of PCVAD and 56 control pigs without PCVAD, revealed that among 10 viruses tested, PCV2 had the strongest association with PCVAD, but the risk for clinical PCVAD was much higher if the pig was concurrently infected with PRRSV (Pogranichniy et al, 2002). Moreover, when proliferative and necrotizing pneumonia cases were tested, concurrent PRRSV and PCV2 infection was confirmed in 40.5% (30/74) of cases in Spain (Grau-Roma and Segalés, 2007), in 41.7% (25/60) in cases in Canada (Drolet et al, 2003) and in 28.6% (8/28) of cases in Italy (Morandi et al, 2010).…”
Section: Porcine Reproductive and Respiratory Syndrome Virusmentioning
confidence: 94%
“…However, there might be relevant to consider vaccination even though naturally acquired antibodies are present, for example in older breeding bitches from about six years age. Here a reactivation may be more likely to cause problems since aging is associated with decreased immune responsiveness and increased susceptibility to infectious diseases [20,35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…Coinfection with other viruses (PRRSV, PCV2, SIV) may result in severe proliferative and necrotizing pneumonia in weanling and postweanling pigs (Morandi et al, 2010). The virus predominantly impacts the respiratory and nervous systems.…”
Section: F Pseudorabiesmentioning
confidence: 99%